Hubungan Gratitude dengan Happiness pada Remaja di Lembaga Kesejahteraan Sosial Anak (LKSA) Al-Maa’uun Yosowilangun Lumajang - Nala Hamidatum Musodiqoh; Wahyu Budi Priyanto; Anugrah Sulistiyowati (Fakultas Dakwah UIN KHAS Jember, 2026)
The various problems experienced by teenagers in LKSA include lack of mental needs fulfillment and emotional problems. This has caused teenagers in LKSA to be unhappy. Nevertheless, happiness can still be felt by teenagers in LKSA even in difficult situations. One of the keys to achievement of happiness is through gratitude for the blessings that have been accepted. The purpose of this study was to determine whether gratitude a relationship with happiness in teenagers at Al-Maa'uun Children's Social Welfare Institution LKSA Yosowilangun Lumajang. This study used a quantitative approach with a correlational type. The number of research samples was 35 adolescents at LKSA Al-Maa'uun Yosowilangun Lumajang uses sampling jenuh. This research instrument used gratitude scale based on theory of Emmons and happiness scale based on Seligman theory. Data analysis techniques used pearson product moment correlation test. The results found that gratitude has a significant positive relationship with happiness in teenagers at LKSA Al-Maa'uun Yosowilangun Lumajang. This is based on the findings of the correlation test results. The significance of 0.007 <0.05 and pearson correlation value of 0.450 > 0.3388 (n-2 = 33) means that the higher gratitude in teenagers, the more happiness felt by teenagers in LKSA Al-Maa'uun Yosowilangun Lumajang.